(untitled) (Journal of Nepal Geological Society, 2000)
The present paper emphasises concerns of land subsidence or compression of clay confining beds caused by periodic withdrawal and injection of water from or into the adjacent aquifers. An analytical solution for a one-dimensional case based on a sandwich model is found so that analysis of potential risk of aquifer system deformation due to the technology of Aquifer Storage and Recovery (ASR) can be conducted. A governing equation expressed directly in terms of displacement is employed to describe the one-dimensional subsidence. For simplicity, saturated aquifer systems are assumed to behave like poroelastic material. A cyclic loading function with a triangle pattern is assumed at boundaries to simulate effective stress induced by changes in hydraulic head at boundaries. The both compression and swelling of clay due to the periodic and linear loads at the boundaries are considered in this model. The two aquifers (one above the confining bed and the other beneath) can be pumped independently of each other. The results from the analytical solution are applied to estimate and predict potential risk of land subsidence due to ASR activity and to provide a first-estimate type of guideline for city or regional development and management of water resources.